(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
The article draws from the scientific debate on the pandemic from Covid19 the adequate perspective in which to look at the concepts of contagion and virus. And it applies it to the spread of mafia organizations in non-traditional areas. It notes the correctness of using the term “contagion”, since not "healthy bodies" but social organisms already weakened by important civil diseases are affected by the virus of the mafia method. The author concludes that the theories oriented to deny validity to the category of contagion appear to be generated by the fear that it could stock the ancient anti-southern ethnic bias rather than by a higher analytical precision.